Cost-effectiveness of carbapenem-resistant Enterobacteriaceae (CRE) surveillance in Maryland. (22nd September 2022) - Lin, Gary; Tseng, Katie K.; Gatalo, Oliver; Martinez, Diego A.; Hinson, Jeremiah S.; Milstone, Aaron M.; Levin, Scott; Klein, Eili
Abstract: Objective: We analyzed the efficacy, cost, and cost-effectiveness of predictive decision-support systems based on surveillance interventions to reduce the spread of carbapenem-resistant Enterobacteriaceae (CRE). Design: We developed a computational model that included patient movement between acute-care hospitals (ACHs), long-term care facilities (LTCFs), and communities to simulate the transmission and epidemiology of CRE. A comparative cost-effectiveness analysis was conducted on several surveillance strategies to detect asymptomatic CRE colonization, which included screening in ICUs at select or all hospitals, a statewide registry, or a combination of hospital screening and a statewide registry. Setting: We investigated 51 ACHs, 222 LTCFs, and skilled nursing facilities, and 464 ZIP codes in the state of Maryland. Patients or participants: The model was informed using 2013–2016 patient-mix data from the Maryland Health Services Cost Review Commission. This model included all patients that were admitted to an ACH. Results: On average, the implementation of a statewide CRE registry reduced annual CRE infections by 6.3% (18.8 cases). Policies of screening in select or all ICUs without a statewide registry had no significant impact on the incidence of CRE infections. Predictive algorithms, which identified any high-risk patient, reduced colonization incidence by an average of 1.2% (3.7 cases) without a registry and 7.0% (20.9 cases) with a registry. Implementation of the registry was estimated to save $572, 000 statewide in averted infections per year. Conclusions: Although hospital-level surveillance provided minimal reductions in CRE infections, regional coordination with a statewide registry of CRE patients reduced infections and was cost-effective.